Influence of Social/Mass Media as a Change Agent on Childhood Social Pedagogy and Achievement - Makinde, Semiu Olawale (Indonesian Journal of Early Childhood Education Studies, 2020)
This study investigated the influence of social/mass media as agent of change on childhood social pedagogy and academic achievement in Lagos, Nigeria. Specifically this study examined the impact of social/mass media on early age children social pedagogy and the aftermath effect on their academic achievement in Lagos, Nigeria. The research design was a descriptive type of survey. The sampling technique adopted was purposive and used to sample the population from upper primary school pupils of age 6 to 9 years. This age range can respond to the instrument of the research with free mind. Respondents to the validated questionnaire of reliability index of 0.87 were 490 pupils of 240 boys and 250 girls from ten Nursery and Primary schools in Ifako Ijaiye, Lagos. Three research objectives were raised for the study. Simple percentages and charts were used to represent and analyse the responses from the respondents. The findings show that the social/mass media especially the android phone and television were powerful devices that influence the lives of early age pupils. It teaches them on how to relate with their environment, improve their performance in school and also a means where they cultivate negative attitudes towards people. Conclusively, the media content effect on young pupils depends on the upbringing, because they react to social/mass media differently and are not influenced the same way. Hence, the type of media contents they exposed to should be monitored in other not to be influenced adversely.